Assessment of Numerical Accuracy and Parallel Performance of OpenFOAM and its Reacting Flow Extension EBIdnsFoam - Zirwes, Thorsten; Sontheimer, Marvin; Zhang, Feichi; Abdelsamie, Abouelmagd; Pérez, Francisco E. Hernández; Stein, Oliver T.; Im, Hong G.; Kronenburg, Andreas; Bockhorn, Henning (Flow, turbulence and combustion, 2023)
OpenFOAM is one of the most widely used open-source computational fluid dynamics tools and often employed for chemical engineering applications. However, there is no systematic assessment of OpenFOAM’s numerical accuracy and parallel performance for chemically reacting flows. For the first time, this work provides a direct comparison between OpenFOAM’s built-in flow solvers as well as its reacting flow extension EBIdnsFoam with four other, well established high-fidelity combustion codes. Quantification of OpenFOAM’s numerical accuracy is achieved with a benchmark suite that has recently been established by Abdelsamie et al. (Comput Fluids 223:104935, 2021. https://doi.org/10.1016/j.compfluid.2021.104935 ) for combustion codes. Fourth-order convergence can be achieved with OpenFOAM’s own cubic interpolation scheme and excellent agreement with other high-fidelity codes is presented for incompressible flows as well as more complex cases including heat conduction and molecular diffusion in multi-component mixtures. In terms of computational performance, the simulation of incompressible non-reacting flows with OpenFOAM is slower than the other codes, but similar performance is achieved for reacting flows with excellent parallel scalability. For the benchmark case of hydrogen flames interacting with a Taylor–Green vortex, differences between low-Mach and compressible solvers are identified which highlight the need for more investigations into reliable benchmarks for reacting flow solvers. The results from this work provide the first contribution of a fully implicit compressible combustion solver to the benchmark suite and are thus valuable to the combustion community. The OpenFOAM cases are publicly available and serve as guide for achieving the highest numerical accuracy as well as a basis for future developments.